CONTENT ANALYSIS OF SELECT COLLEGE LIBRARY WEBSITES OF JAWAHARLAL NEHRU TECHNOLOGICAL UNIVERSITY, HYDERABAD: A STUDY - Mustafa, Faisal; Khan, Javed (International Journal of Research -GRANTHAALAYAH, 2023)
The study assesses ten select library websites from colleges affiliated with JNTU, Hydera-bad, for their usability, correctness, and accessibility. Additionally, it discusses the features and services offered by websites. A well-organized checklist was used to collect data from the study’s selected colleges. According to the survey, the majority of colleges have included information about their services (80%) and infrastructure (80%) on their websites, and all libraries of selected colleges have incorporated details about their introduction (100%) collection (100%), and statistics (100%). However, the report did point out that none of the library websites or web pages have a section for people with disabilities, a user manual, a single window search, an Ask a librarian link, newspaper clippings, remote access, interlibrary loan (ILL)/document delivery, social networking facilities, or regular updates. They also fall short in terms of accessibility. The study’s findings indicate that Sultanul Uloom College of Pharmacy and Shadan Wom-an’s College of Pharmacy received the lowest score of six (06) out of forty-three (43) and are currently ranked last, while the library at Aurora’s Scientific, Technological and Re-search Academy had the highest score of twenty-two (22) out of forty-three (43), and is currently ranked first. The paper offers suggestions for carrying out these assessment studies, which are critically required to allow organization to continually update their website and deliver better results in terms of user requirement.